Synthesis and Characterization of Thiadiazolo[3,4-g]quinoxaline Based p-Conjugated Copolymers with Tunable Band Gaps - Tao, Feng; Wang, Zheng; Li, Zuojia; Li, Kai; Li, Ying; Peng, Qiang (Asian Journal of Chemistry, 2013)
A series of alternating conjugated copolymers based on thiadiazolo[3,4-g]quinoxaline units and different electron-donating units, such as fluorene, benzene and thiophene, with donor (D)-acceptor (A) alternating structures have been synthesized by palladium catalyzed Sonogashira condensation polymerization. The resulting copolymers P1, P2 and P3 were characterized by NMR, IR, gel permeation chromatography, thermogravimetric analysis and differential scanning calorimetry. Their optical and electronic properties can be facilely fine-modulated by adjusting the structures of different aromatic or heteroaromatic blocks. UV-visible absorption and cyclic voltammetry measurements indicate that all these copolymers have low band gaps due to the strong interaction between the donor and thiadiazolo[3,4-g]quinoxaline segments. Polymer P1 exhibits highest HOMO energy level, which can be expected to obtain high open-circuit voltage (Voc) from the fabricated PSCs. Polymer P3 based on thiophene and thiadiazolo[3,4-g]quinoxaline show smallest band gap and best absorption of sun light even in near-infrared (NIR) region. Preliminary studies imply that these copolymers can be used as efficient polymer donor materials in polymer solar cell applications.